A human-centred intelligent system framework: meta-synthetic engineering. (21st February 2008) - Cui, Xia; Dai, Ruwei
From the viewpoint of knowledge and intelligence, to bridge data mining and agents, this paper deal with an efficient way that is building intelligent systems by means of meta-synthesis proposed by Chinese scientists, which is used multiple human intelligence implantations for intelligent system, take full advantage of agents as well as analysis and meta-synthesis. Such systems combine the qualitative?quantitative intelligence in knowledge conductive and human-centred Cooperative Problem-Solving (CPS), involving human centred Cooperative Problem-Solving (CPS), meta-synthetic engineering techniques, human?human interactions and organisation based on group thinking technology, Human?Computer Interactions (HCI), and computer?computer interactions based on agents technology.